Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Kota Palembang Dalam Memilih Asuransi Jiwa Syariah - Allinaida Pratiwi; Ulil Amri (Journal of Economics and Development, 2024)
Company image, premium prices and products are important factors and are the goals of every company, including those in the insurance sector. Apart from being an important factor as the front guard for the continuity of the company's operation, the existence of this factor can support increasing public interest in insurance, especially sharia life insurance in the city of Palembang. The research conducted aims to determine the influence of company image, premium prices and products on people's interest in choosing sharia life insurance in the city of Palembang where the focus is on sharia life insurance customers in the city of Palembang who are or have been sharia life insurance customers in the city of Palembang as the population. The method used in collecting data is through a questionnaire using a Likert scale. Through the characteristics of sharia insurance users with a period of less than 1 year to more than 5 years and customers who have not yet become customers. The sample consisted of 120 respondents using purposive sampling technique. The Path Coefficient shows that Company Image and Products have a positive and significant influence on public interest. Meanwhile, the premium price has no positive and significant effect on people's interest in choosing sharia insurance in the city of Palembang.